The presence of fine and ultrafine particulate matter in the work environment - Adamec, Vladimír; Köbölová, Klaudia; Urbánek, Michal; Čabanová, Kristina; Bencko, Vladimír; Tuček, Milan (Central European journal of public health, 2020)
This study presents the results of pilot measurement, where the exposure of fine and ultrafine particulate matter was monitored. The measurement was performed in welding workplace, where these particles are produced unintentionally. The measurement consisted of collecting information and measuring the concentration of particles in the workplace, where data collection was focused only on inhalation exposure. During welding, primarily 300 nm size particles are produced, and their concentration is strongly influenced by the welding material, type of welding and suction. The particles are amorphous in terms of morphology and contain manganese, iron and silicon, which can cause neurodegenerative diseases. Furthermore, the results indicate the importance of monitoring oral exposure.
Keywords: health; risk assessment; Humans; pracoviště; látky znečišťující vzduch v pracovním prostředí; lidé; Welding; work environment; Air Pollutants, Occupational; Workplace; Particulate Matter; fine and ultrafine particulate matter; svařování; pevné částice